PEMAHAMAN ANAK DAN ORANG TUA TERHADAP KEKERASAN BERBASIS ELEKTRONIK: PELACAKAN TERHADAP PEMBENTUKAN AGENDA SETTING TERKAIT KEKERASAN BERBASIS ELEKTRONIK DARI MASYARAKAT - Ishmah, Nadhilah -; Alfirdaus, Laila -; Marlina, Neny - (Journal of Politic and Government Studies, 2025)
Electronically mediated violence or digital bullying, a form of electronically mediated violence targeting children, is an increasingly urgent issue as internet usage among young people grows. This study investigates how societal engagement can significantly contribute to addressing electronically mediated violence, particularly digital bullying, through policy responses. Emphasizing the critical role of community involvement via advocacy initiatives, collaborative partnerships, and stakeholder engagements ensures that this issue garners governmental attention. Furthermore, the study examines parental and child understanding of electronically mediated violence and its influence on the formation of protective policies within child safeguard frameworks. Utilizing a descriptive qualitative approach, the study incorporates insights derived from extensive interviews with key informants. Findings reveal that communities are becoming more aware of the importance of preventing digital bullying and other forms of electronically mediated violence. However, a gap remains between awareness and practical actions, such as reporting incidents or implementing preventive measures. Existing regulations are often too vague to address digital bullying effectively. To create a safe digital environment for children, collaboration among various stakeholders is essential. Comprehensive policies should include prevention strategies, legal enforcement, and recovery programs. This study is expected to serve as a foundation for future research and policy development while encouraging community-driven prevention and advocacy initiatives